2005
DOI: 10.1681/asn.2004110917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Anti-DNA Antibodies on Proximal Renal Tubular Epithelial Cell Cytokine Expression

Abstract: This study aimed to investigate the effects of human anti-DNA antibodies (Ab) from patients with lupus on renal proximal tubular epithelial cells (PTEC), focusing on alterations in cell morphology and proinflammatory cytokine synthesis. Immunohistochemistry showed increased tubulointerstitial IL-6 expression and IgG deposition in renal biopsies from patients with diffuse proliferative lupus nephritis, not observed in controls or membranous lupus nephritis, which correlated with the severity of inflammatory cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 41 publications
(45 reference statements)
1
86
0
Order By: Relevance
“…This is worthy of further investigation in view of the accumulating data on the direct interaction between anti-DNA antibodies and resident kidney cells. 30,31 In conclusion, the results from our studies show that rapamycin is effective in ameliorating aberrant immune hyperactivity and preventing the development of lupus nephritis in the NZB/W F 1 mouse. Further studies are warranted to examine the effect of rapamycin in the treatment of florid disease and its role in the treatment of human lupus.…”
Section: Discussionmentioning
confidence: 62%
“…This is worthy of further investigation in view of the accumulating data on the direct interaction between anti-DNA antibodies and resident kidney cells. 30,31 In conclusion, the results from our studies show that rapamycin is effective in ameliorating aberrant immune hyperactivity and preventing the development of lupus nephritis in the NZB/W F 1 mouse. Further studies are warranted to examine the effect of rapamycin in the treatment of florid disease and its role in the treatment of human lupus.…”
Section: Discussionmentioning
confidence: 62%
“…[20][21][22][23][24][25] Some investigators proposed different pathogenic mechanisms inducing tubulointerstitial injury in experimental and human lupus nephritis. These factors include immune complex deposition, 23,26,27 albuminuria macrophage chemokines, 28-33 some autoantibodies, 34,35 and others. 36 Recent studies suggested that activation of tubular Toll-like receptor-9 had a pathogenic role in tubulointerstitial inflammation and damage in lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of anti-DNA antibodies in the pathogenesis of autoimmune glomerulonephritis in lupus mice has been well documented [21]. It was recently demonstrated that anti-DNA antibodies bound to mesangial cells and proximal renal tubular epithelial cells, and were rapidly internalized following cell surface binding [22,23]. This was associated with a proliferative response, decreased cell viability, and increased synthesis of extracellular matrix components and pro-inflammatory cytokines such as IL-6 and TNF-α [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that anti-DNA antibodies bound to mesangial cells and proximal renal tubular epithelial cells, and were rapidly internalized following cell surface binding [22,23]. This was associated with a proliferative response, decreased cell viability, and increased synthesis of extracellular matrix components and pro-inflammatory cytokines such as IL-6 and TNF-α [23]. It has also been reported that mouse anti-dsDNA antibodies penetrate mouse macrophage cells and stimulate nuclear factor-kappa B activation and TNF-α release [24].…”
Section: Discussionmentioning
confidence: 99%